Establishment of a limited liability company by church legal entities conducting charity and care activities - Poniatowski, Michał (Prawo Kanoniczne, 2023)
This article contains an analysis of the issue of establishing a limited liability company by church legal entities conducting charity and care activities. The first part of the article examines the right to form such companies by these church legal entities. The next part analyzes the scope of a limited liability company, while the last part refers to the specifics of establishing such a company by a church legal entity conducting charitable and caring activities. The most important conclusions are at the end.